Genetic parameters for mouth size and their influence on growth traits in pasture-raised Nelore cattle - Dominguez-Castaño, Pablo [UNESP]; Maiorano, Amanda Marchi; Lopes, Jose Eduardo Silva [UNESP]; De Oliveira, Matheus Henrique Vargas [UNESP]; Castilhos, Andre Michel [UNESP]; Silva, Josineudson Augusto Ii Vasconcelos [UNESP] (Oxford University Press (OUP), 2023)
Evaluating traits that allow breeders to increase production efficiency in beef production systems is important. The mouth size (MS) score is a trait easily measured and implemented by breeders. Bite size is related to MS in beef cattle and is a determinant of daily feed intake of pasture-raised animals, influencing their growth. The aim of this study was to estimate genetic parameters for MS, weaning weight (WW) and postweaning weight gain (PWG) of Nelore cattle and to evaluate the influence of the interaction between MS and WW on PWG. Phenotypic records of 134,282 Nelore animals born between 1995 and 2019 were used. Variance components were estimated using multitrait animal model with the Bayesian method. The model included the contemporary group as fixed effect, age at measurement of the trait as linear covariate, and direct additive genetic and residual effects as random effects. For WW, random maternal and maternal permanent environmental effects were added to the model. A Bayesian approach was used to analyze the interaction between WW clusters and MS. The heritability estimates were 0.24, 0.15, and 0.23 for MS, WW, and PWG, respectively. The genetic correlation between variables studied ranged from 0.24 to 0.46. The results suggest that animals with a larger mouth tend to have greater PWG, demonstrating the positive influence of MS score on the postweaning performance of cattle. The direct heritability estimates confirm the possibility of selecting animals for the traits studied.
Keywords: bite; genetic correlation; heritability; weaning weight; weight gain